Evaluation of confirmatory data following the Article 12 MRL review for S‐metolachlor - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; German Giner Santonja; Luna Greco; Samira Jarrah; Renata Leuschner; Javier Martinez Perez; et al. (EFSA Journal, 2023)
Abstract The applicant Syngenta Crop Protection AG submitted a request to the competent national authority in Germany to evaluate the confirmatory data that were identified for S‐metolachlor in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, a new freezer storage stability study for S‐metolachlor in commodities with high acid content was submitted. However, the data gap on storage stability was considered only partially addressed for strawberries because, in the absence of information on the storage time interval of the samples of the residue trials performed on strawberries, no conclusion on the validity of these trials could be drawn. The data gap on the lack of trials to support the good agricultural practice (GAP) on pineapples was not addressed. Consequently, the existing tentative MRLs for strawberries and pineapple cannot be confirmed and EFSA recommends lowering these MRLs to the enforcement limit of quantification (LOQ). Since a new lower LOQ for enforcement in high acid content commodities of 0.01 mg/kg has been validated, it is proposed to change the existing MRL value from 0.05* to 0.01* mg/kg for these two commodities.